A case of canine idiopathic eosinophilic meningoencephalitis with serial MRI scans, CSF analyses and histopathology. Issue 1 (2nd May 2017) - Cowan, Allison; Bibevski, Jennifer; Axlund, Todd
Abstract : A six‐year‐old labrador retriever mix was evaluated for behaviour change, hyperaesthesia and inappropriate urination. Neurological examination was consistent with a multifocal localisation. Multiple MRI scans, cerebrospinal fluid (CSF) analyses, infectious disease titres and a cerebral biopsy were performed over the course of nine months, confirming the diagnosis of idiopathic eosinophilic meningoencephalitis. The patient was treated with immunomodulatory medications, antibiotics, anthelminthics and anticonvulsant medications. Resolution of meningoencephalitis was achieved; however, permanent neurological deficits remained and seizures became more difficult to control. The patient's neurological status was followed until her death approximately six years following initial presentation. This is the first and only reported case of idiopathic eosinophilic meningoencephalitis to have had multiple MRI scans and CSF analyses performed. This report allows for visual tracking of disease progression and correlates it with CSF characteristics and clinical signs. Furthermore, this report demonstrates the persistent long‐term ramifications of the disease, even after successful treatment.